GAMBARAN PENYAKIT GINGIVITIS PADA PASIEN YANG BEKUNJUNG KE POLI GIGI RUMAH SAKIT (Politeknik Kesehatan Kemenkes Bandung, 2020)
Gingivitis is inflammation of the gums that is characterized by changes in the shape and color of the gums to bright red, bleed easily, and the swelling of the gums. This condition is caused by irritation from plaque that has accumulated around the gums. The purpose of this study was to determine the incidence of Gingivitis in dental dentistry at the Regional General Hospital of Prabumulih City. This type of research is to use literature study research with descriptive methods. The sample of this research were all patients who came to the dental clinic of the General Hospital of Prabumulih City as many as 1284 people. Data collection methods are obtained by using secondary data, namely supporting data obtained by researchers from existing sources which are then processed using a frequency distribution table. The results of this study are those who suffer from Gingivitis as many as 228 people (17.8%), seen from the male gender as many as 121 people (53.1%) and 107 women (46.9%), while viewed from the age of 35 years 48 people (21%). It can be seen that in dental clinics in the Prabumulih City Regional General Hospital 2017, there are many who suffer from Gingivitis at the age of 20-35 years and are male. Key words: gingivitis, dental clinic